Application of nearest neighbour search techniques to peptide identification from mass spectrometry - Ulate-Cárdenas, José de Jesús (Instituto Tecnológico de Costa Rica, 2018)
We explored if the application of Nearest Neighbour Search thecniques to the de novo sequence of amino acids from Tandem Mass Spectrometry will provide better performance and accuracy. We present an indexation strategy that allows a posterior interpretation of the spectral data using concepts of Topology. We also offer an analysis of the execution time and space needed for both strategies.
Proyecto de Graduación (Maestría en Computación) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Computación, 2018.
Keywords: Técnicas; Identificación; Topología; Análisis; Tiempo